Effect of volcanic ash over Orthoptera survival in Patagonia - Fernandez Arhex, Valeria Cristina; Amadio, Maria Emilia; Enriquez, Andrea Soledad; Pietrantuono, Ana Laura; Becker, Guillermo Fernando; Bruzzone, Octavio Augusto (2017)
The aim of this work was to evaluate the ash toxicity from the Puyehue-Cordón Caulle volcanic complex on the survival of two Orthopteran species: the grasshoper Dichroplus vittigerum and the green locust Brugilis sp. Two grain size were used to evaluate the effect of volcanic eruption on these insects. Chemical analyses from this eruption proved that the ashes were very abrasive and predominantly composed of silica shards (SiO2 ) and aluminia (Al2 O3 ), two substances with insecticidal properties. In northern Patagonia, both orthopteran species are polyphagous chewers on grasses and dicots. The laboratory data showed that sustained exposure to volcanic ash induced mortality in adult grasshoppers. Survival of D. vittigerum significantly decreased once exposed to the two ash granulometries. In turn, Brugilis sp. survival was significantly reduced when exposed to fine grain ashes. These results suggest that the onset of the volcanic eruption with the consequent suspension of the pyroclastic material in the air might negatively impacted these orthopteran due to the mortality of adults. The ash from the Puyehue-Cordón Caulle volcanic complex could be compared to the application of non-persistent and broad spectrum insecticide, causing a temporary reduction in orthopteran populations.